2018
DOI: 10.3390/su10020323
|View full text |Cite
|
Sign up to set email alerts
|

A Kitchen with too Many Cooks: Factors Associated with Hospital Profitability

Abstract: Abstract:In this paper, we carefully investigate previous literature to extract 10 relevant factors to explain the hospital profitability and build an econometrically well-specified model of explaining hospital profitability that does not suffer from omitted variable bias. Then we provide empirical evidence to a common belief that the objective function of a hospital varies with the type of hospital. We identified distinct objective functions for three types of hospitals: for-profit hospitals are driven by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Numerous previous studies, conducted in different countries, indicated that the type of ownership might be an important factor determining hospital financial performance [8,37,38]. Our study focused solely on public hospitals, thus, the scope of owners was limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies, conducted in different countries, indicated that the type of ownership might be an important factor determining hospital financial performance [8,37,38]. Our study focused solely on public hospitals, thus, the scope of owners was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Financially stable hospitals are better able to maintain reliable systems and provide resources for quality improvement [1]. Therefore, monitoring financial performance of heath care units is important in the context of improving efficiency and securing the organizational sustainability of care provision [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies were excluded because the reference categories in their estimations did not strictly compare public and private management, (i.e. Thorpe et al 2001;Lien et al 2008;Czypionka et al 2014;Cavallieri et al 2018;Cho & Hong 2018). Other studies had to be excluded because the authors did not provide enough statistical information to include in the final database.…”
Section: --Insert Table 1 About Here --mentioning
confidence: 99%
“…Teaching hospitals tend to offer a more complex range of medical services than non-teaching organizations, including tertiary care services, and thus, they are more likely to attract patients with severe diagnoses [42]. The ratio of Medicaid and Medicare patients tend to have a complicated health status or a chronic disease [50].…”
Section: Control Variablesmentioning
confidence: 99%